2008
DOI: 10.1007/s11064-008-9653-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of NCAM in Spine Dynamics and Synaptogenesis

Abstract: Increasing evidence indicates that adhesion molecules are critically involved in the regulation of mechanisms of synaptic plasticity including synapse formation, but also synaptic remodeling associated to changes in synaptic strength. Among these, the Neural Cell Adhesion Molecule (NCAM) and its polysialylated form PSA-NCAM are important candidates. Here we review recent results that point to a possible role of these two molecules in regulating the structural properties of excitatory synapses and namely the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Since PSA-NCAM is a major player in structural plastic processes such as neurite elongation, cell migration and synaptogenesis as well as synaptic remodelling (Muller et al, 2008 ;Rutishauser and Landmesser, 1996 ;Seki and Rutishauser, 1998), which are compromised in schizophrenia (Frost et al, 2004), we can hypothesize a beneficial effect of olanzapine on neuroplastic deficits in mPFC through changes in synaptic structure and connectivity, perhaps mediated by an increase of PSA-NCAM. Although we did not investigate the cellular phenotype of PSA-NCAM-expressing cells, it has recently been demonstrated that PSA-NCAM immunoreactive cells in the mPFC are probably GABAergic interneurons (Varea et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Since PSA-NCAM is a major player in structural plastic processes such as neurite elongation, cell migration and synaptogenesis as well as synaptic remodelling (Muller et al, 2008 ;Rutishauser and Landmesser, 1996 ;Seki and Rutishauser, 1998), which are compromised in schizophrenia (Frost et al, 2004), we can hypothesize a beneficial effect of olanzapine on neuroplastic deficits in mPFC through changes in synaptic structure and connectivity, perhaps mediated by an increase of PSA-NCAM. Although we did not investigate the cellular phenotype of PSA-NCAM-expressing cells, it has recently been demonstrated that PSA-NCAM immunoreactive cells in the mPFC are probably GABAergic interneurons (Varea et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…NCAM1 is one of the first molecules to accumulate at forming synapsis, promoting membrane binding between neurons and the stabilization of the connection. Indeed, the overexpression of the protein led to a stimulation of the formation of synapses while a deficiency results in a reduction in the total volume of dendritic spines [ 58 , 59 , 60 ]. NCAM1 is important not only for synapse formation but also for the regulation of synapse dynamics due to its interaction with different cytosolic (e.g., actin and microtubules cytoskeleton) and membrane components from the presynaptic and postsynaptic compartments [ 56 , 57 , 58 , 59 , 60 , 61 , 62 ].…”
Section: Introductionmentioning
confidence: 99%
“…NCAM180 and NCAM140 are transmembrane isoforms, while NCAM120 is attached to the membrane via a glycophosphatidylinositol anchor. Functional triggering of NCAM leads to neural cell migration, neurite outgrowth and fasciculation, synaptogenesis, synaptic plasticity, and certain forms of emotional behavior, thus most likely implicating different molecular mechanisms in signaling (for reviews, see Brennaman and Maness, 2010;Conboy et al, 2010;Ditlevsen and Kolkova, 2010;Muller et al, 2010). Homophilic or heterophilic interactions between NCAM and its extracellular binding partners, in particular with fibroblast growth factor (FGF) receptors (for review, see Kiselyov, 2010) and glial cell line-derived neurotrophic factor (GDNF) receptor (Paratcha et al, 2003), trigger NCAMdependent intracellular signaling events resulting in these distinct cellular responses.…”
Section: Introductionmentioning
confidence: 99%